Clusters and resilience during the COVID-19 crisis: Evidence from Colombian exporting firms - Mercedes Campi; Marco Due\~nas (Inter-American Development Bank (IDB), 2022)
In this paper, we characterize the geography of Colombian exporting clusters and analyze how the COVID-19 crisis has affected Colombian exporters. We contribute to the industrial clusters literature by defining exporting clusters with bipartite network analysis and community detection tools. The methodology allows us to empirically detect product clusters, which are compared with an alternative definition of industrial clusters, and to consider the centrality of firms within clusters. Then, we analyze the firms' trade margins during the COVID-19 crisis to evaluate whether belonging to an exporting cluster can be a source of resilience for firms. We find that clusters do not automatically lead to higher resilience and that there are differences in how firms react to a crisis within clusters. Identifying the relevant firms' characteristics can guide policymakers to activate the mechanisms that generate resilience.
Keywords: F14; R12; L19; 330; exporting clusters; margins of trade; resilience; COVID-19; bipartite networks; community detection